2022
DOI: 10.1021/acsomega.2c03591
|View full text |Cite
|
Sign up to set email alerts
|

Steric Effects in the Deposition Mode and Drug-Delivering Efficiency of Nanocapsule-Based Multilayer Films

Abstract: Using surface-initiated atom transfer radical polymerization (ATRP), block polymers with a series of quaternization degrees were coated on the surface of silica nanocapsules (SNCs) by the “grafting-from” technique. Molnupiravir, an antiviral medicine urgently approved for the treatment of SARS-CoV-2, was encapsulated in polymer-coated SNCs and further incorporated into well-defined films with polystyrene sulfonate (PSS) homopolymers by layer-by-layer (LBL) self-assembly via electrostatic interactions. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…A large number of Gram-negative and Gram-positive bacteria can be effectively inhibited from growth by NS [29,30]. Previous studies have shown that biobased composites are not only efficient in encapsulating drug reagents and releasing functional molecules in a controlled mode, but also possess good biocompatibility and biodegradability [31,32]. In order to inhibit the bacteria that are resistant to multiple drugs and to prohibit pathological inflammation, NS was chosen by other groups to be incorporated in thin films to develop efficient antibiotic coatings [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of Gram-negative and Gram-positive bacteria can be effectively inhibited from growth by NS [29,30]. Previous studies have shown that biobased composites are not only efficient in encapsulating drug reagents and releasing functional molecules in a controlled mode, but also possess good biocompatibility and biodegradability [31,32]. In order to inhibit the bacteria that are resistant to multiple drugs and to prohibit pathological inflammation, NS was chosen by other groups to be incorporated in thin films to develop efficient antibiotic coatings [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The good biocompatibility of PMMA and incorporation of nanoparticles broadens this field even further. Taking a look at the work of Xu et al, drug delivery systems of self-assembling block polymers containing silica nanocapsules filled with drugs for cancer or Covid treatment show promising novel applications, although their approach also benefits from stimuli-responsivity, which is not included in this work. Modification of the methoxy group allows even further extension of these possible fields of application, opening up toward life-science applications like cell-separation (i.e., Fab-TACS technology from IBA) just to name one example in this field. , …”
Section: Introductionmentioning
confidence: 99%
“…2 EU regulation No 10/2011 lays down restrictions and specifications on the use of certain substances to determine the conformity of plastic materials and articles intended to come into contact with food. 11 Over the past decades, nanotechnologies have demonstrated their applicability in various fields, particularly in the medical industry for the controlled release of active substances through multilayer films, with potential applications in the treatment of COVID-19 and lung cancer [12][13][14] In addition, nanotechnologies have showed their effectiveness in the field of food packaging, providing innovative solutions to prevent or reduce the migration of unreacted monomers and molecular additives from packaging materials up to food. 15 In addition to reducing interactions with food, the incorporation of nanoparticles into packaging materials allows improving several other key properties such as: antimicrobial properties, gas barrier properties, mechanical properties, temperature stability, and so forth.…”
Section: Introductionmentioning
confidence: 99%